PREVALENCE OF CARDIAC RISK FACTORS IN PATIENTS WITH ABDOMINAL AORTIC ANEURYSM - V. S. Arakelyan; A. R. Jane; N. A. Gidaspov; P. P. Kulichkov; N. V. Bortnikova («REMEDIUM GROUP» Ltd., 2019)
Introduction. According to the literature, 27 to 65 % of patients with abdominal aortic aneurysm also suffer from coronary heart disease. Mortality from coronary heart disease after surgical treatment for abdominal aortic aneurysm according to some data exceeds 20 %.Objective: improvement of results of treatment of patients with combined lesions of coronary arteries and aneurysm of the abdominal aortaSubjects and method. A retrospective analysis of case histories of 100 patients hospitalized in our clinic diagnosed with «abdominal aortic aneurysm» for examination. Of all patients, 37 % were diagnosed with significant coronary artery lesions. The average ejection fraction was 58.2 ± 5.4 %, 13 % of the study diagnosed significant violations of local myocardial contractility. 16 % of patients had previous myocardial infarction, 7 % - a permanent form of atrial fibrillation. 4 % of patients complained of chest pain during exercise. Hypertension was present in 100 % of patients, the average maximum systolic blood pressure was 176 ± 24.5 mmHg.Results. Hospital mortality was 2 % (all patients were non-operated on coronary arteries and had no significant coronary pathology). There were no significant complications (cardiac, neurological, respiratory) in the early postoperative period. The average length of hospital stay was 9.8 ± 1.99 bed days.Conclusions. Determination of cardiac status before surgery for abdominal aortic aneurysm is the most important moment of stratification of the risk of perioperative complications. Coronary angiography in patients with abdominal aortic aneurysm is a mandatory point of diagnosis, allowing to identify cardiac risk factors.